The Role of Principal Leadership: Developing Reading Culture in Elementary School - Fadlilah, Fadlilah; Chaniago, Fransisko; Fitriani, Suci; Sakunti, Sri Ramdayeni (Jurnal Paedagogy, 2022)
This study aims to explore the principal leadership role in developing the reading culture at the Public Elementary School No. 42 Pekan Gedang, Batang Asai District. This study employed qualitative method, where data collection was done through observation and interview with a number of informants such as; school principal, teachers, and students as well as the canteen community nearby the school. Triangulation was used as a method for qualitative data analysis and validating the data collected Triangulation was used as a method for qualitative data analysis and validating the data collected. The results of this study revealed that in order to cultivate a reading culture among the kids, the principal implemented a program known as Jumpa Sinabu. This program was carried out on Friday mornings with the activities of reciting Al-Qur’an and reading books before the teaching and learning processes begin. In addition, the principal encourages other members of the school community, including teachers, employees, and even canteen residents who sell around the school building to involve and support to the program that the principal has developed. At the Public Elementary School No. 42 Pekan Gedang, the principal’s leadership in developing a reading culture is as a policy maker, facilitator, and motivator. These all are part of the process of creating a reading culture.